Participatory design of healthcare facilities using virtual reality - Springer, Piotr (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
This paper is an attempt to explore the possibilities of using Virtual Reality within participatory design of healthcare facilities. The aim of this work is to determine fields in which technologically advanced participatory design tools may improve integrated design. As a part of research, a scientific literature review and an analysis of existing medical facilities have been made, especially in the context of influence that building function have on the process of its programming and designing.